Splenic artery aneurysm - TCBC-RJ,RUI ANTÔNIO FERREIRA, (2016)
ABSTRACT Splenic artery aneurysms - the most common visceral artery aneurysms - are found most often in multiparous women and in patients with portal hypertension. Indications for treatment of splenic artery aneurysm or pseudoaneurysm include specific symptoms, female gender and childbearing age, presence of portal hypertension, planned liver transplantation, a pseudoaneurysm of any size, and an aneurysm with a diameter of more than 2.5cm. Historically, the treatment of splenic artery aneurysm has been surgical ligation of the splenic artery, ligation of the aneurysm, or aneurysmectomy with or without splenectomy, depending on the aneurysm location. There are other percutaneous interventional techniques. The authors present a case of a splenic artery aneurysm in a 51-year-old woman, detected incidentally.